Borehole Diameter Inspection for Hard Disk Drive Pivot Arms Using Hough Transform in Panorama Images - Sansanee Auephanwiriyakul (2018)
© 2015 John Wiley & Sons, Inc. All Rights Reserved. The dimension measurement of a hard disk drive (HDD) component is an important process in the HDD industry, which is one of the most prolific industries in Thailand. This chapter focuses on a borehole dimension inspection of HDD pivot arms, using an automated dimension inspection system. This system is operated on graylevel images. The color images from a microscope are converted to graylevel images using luminance (Y) component. The chapter discusses a feature-based panoramic image construction method. It then focuses on the dimension estimation of the borehole using the Hough transform (HT). The chapter further presents some of the experiment results. The results highlight that the performance of both borehole panorama image construction and HT in swage hole dimension inspection are efficient. The HT performs quite satisfactorily in estimating the diameter.